RESPON PERTUMBUHAN DAN KANDUNGAN FENOLIK KUNYIT KUNING (Curcuma domestica Val.) DENGAN PEMBERIAN EKSTRAK BAWANG BOMBAY MERAH (Allium cepa L.) - Nike Nur Fadilah; Mirwa Adiprahara Anggarani (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[IMPACT OF RED ONION EXTRACT ON THE GROWTH AND QUALITY RHIZOMES OF YELLOW TURMERIC (Curcuma domestica Val.)]. Turmeric, a member of the Zingiberaceae family, is known for its richness in phenolic compounds with antioxidant activity and is often utilized as a raw material in traditional medicine. However, the productivity of turmeric experiences a decline, and a dormancy period occurs during the dry season, demanding solutions to overcome these challenges. Agricultural intensification is considered an alternative to enhance the growth and secondary metabolite yield by applying natural Plant Growth Regulators (PGRs). Red onion possesses phytohormones that hold potential as natural PGRs. This research aims to evaluate the impact of the most effective of red onion extract in enhancing the growth and rhizome quality of yellow turmeric. The experiment was conducted using a Randomized Complete Block Design (RCBD) with variations in extract concentrations (0%, 2.5%, 5%, 7.5%, and 10%). Variables measured included plant height, leaf count, number of yellow turmeric seedlings, rhizome weight, total phenolic content, and antioxidant activity. Result analysis was carried out using Analysis of Variance (ANOVA), followed by a DMRT test at a significance level of 5%. The findings indicate that the red onion extract significantly affects all observed variables, except for the number of shoots. The 10% red onion extract treatment demonstrated the most positive impact on all measured variables.